2008
DOI: 10.1016/j.febslet.2008.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Human neprilysin‐2 (NEP2) and NEP display distinct subcellular localisations and substrate preferences

Abstract: Neprilysin-2 (NEP2) is a novel metallopeptidase homologous to neprilysin (NEP), an enzyme involved in regulation of neuropeptide signalling. NEP2 exists as two alternatively spliced isoforms, NEP2 and NEP2 D . In this study, we cloned and expressed both human isoforms. Human NEP2 exists as a membrane-bound and soluble enzyme, whereas human NEP2 D exists as two membrane-bound glycoforms, localised to the ER and plasma membrane. Surprisingly, NEP2 substrate specificity and inhibitor binding was distinct from tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…Nevertheless, in addition to comparable inhibitor susceptibilities the two enzymes exhibit quite similar substrate specificities. In line with Drosophila NEP4 (this work), the main substrates cleaved by human NEP2 are substance P and angiotensin I (Whyteside and Turner, 2008). The fact that human NEP and NEP2, despite completely conserved subsite residues, exhibit major differences in their specificities clearly indicates that residues other than those mentioned above are responsible for regulating access to the catalytic center.…”
Section: Nep4 Exhibits Enzyme Characteristics Similar To Mammalian Nep2mentioning
confidence: 72%
See 2 more Smart Citations
“…Nevertheless, in addition to comparable inhibitor susceptibilities the two enzymes exhibit quite similar substrate specificities. In line with Drosophila NEP4 (this work), the main substrates cleaved by human NEP2 are substance P and angiotensin I (Whyteside and Turner, 2008). The fact that human NEP and NEP2, despite completely conserved subsite residues, exhibit major differences in their specificities clearly indicates that residues other than those mentioned above are responsible for regulating access to the catalytic center.…”
Section: Nep4 Exhibits Enzyme Characteristics Similar To Mammalian Nep2mentioning
confidence: 72%
“…Thiorphan in particular has frequently been used to inhibit neprilysin-like activity and is reported to be neprilysin specific at nanomolar concentrations (Turner et al, 2001). The observation that in contrast to human NEP, human NEP2 (Whyteside and Turner, 2008) but also Drosophila NEP4 (Fig.6D) are relatively resistant against these two inhibitors could be an indication of similarities in the structure of their active sites. Despite distinct differences in substrate specificity and inhibitor sensitivity (Whyteside and Turner, 2008), a comparison of the amino acid residues that line the hydrophobic pockets of human NEP (Oefner et al, 2000;Oefner et al, 2004) and human NEP2 (Whyteside and Turner, 2008) showed identical ligand binding S 1 Ј and S 2 Ј subsites (Table1).…”
Section: Nep4 Exhibits Enzyme Characteristics Similar To Mammalian Nep2mentioning
confidence: 99%
See 1 more Smart Citation
“…V) at the P1' position (summarized from MEROPS; Rawlings et al 2012). In mammals, individual Neps tend to have very specific substrate affinities despite sharing conserved active site residues, suggesting that this specificity is based on other sequence features (Johnson et al 2002;Rose et al 2002;Bland et al 2008;Whyteside and Turner 2008). Although the cleavage specificities of Drosophila neprilysins are not as well known, there is evidence that Drosophila Nep2 is capable of cleaving locust, human, and fly tachykinins in vitro.…”
Section: Distribution and Potential Targets Of Neprilysins In D Melamentioning
confidence: 99%
“…A Nep2 null allele, Nep2D, was generated by means of a deletion generator compound element as described in (Huet et al 2002). The starting stock was yw;;P (Whyteside and Turner 2008) DG19304. Loss of transcript was confirmed by qRT-PCR.…”
Section: In Situ Hybridizationmentioning
confidence: 99%